Inhibition of carbohydrate hydrolyzing enzymes by a potential probiotic Levilactobacillus brevis RAMULAB49 isolated from fermented Ananas comosus - Martiz, Reshma Mary; Kumari V. B., Chandana; Huligere, Sujay S.; Khan, Mohd Shahnawaz; Alafaleq, Nouf Omar; Ahmad, Saheem; Akhter, Firoz; Sreepathi, Navya; P., Ashwini; Ramu, Ramith (Frontiers in Microbiology, 2023)
The research aimed to explore the potential probiotic characteristics of Levilactobacillus brevis RAMULAB49, a strain of lactic acid bacteria (LAB) isolated from fermented pineapple, specifically focusing on its antidiabetic effects. The importance of probiotics in maintaining a balanced gut microbiota and supporting human physiology and metabolism motivated this research. All collected isolates underwent microscopic and biochemical screenings, and those exhibiting Gram-positive characteristics, negative catalase activity, phenol tolerance, gastrointestinal conditions, and adhesion capabilities were selected. Antibiotic susceptibility was assessed, along with safety evaluations encompassing hemolytic and DNase enzyme activity tests. The isolate's antioxidant activity and its ability to inhibit carbohydrate hydrolyzing enzymes were examined. Additionally, organic acid profiling (LC-MS) and in silico studies were conducted on the tested extracts. Levilactobacillus brevis RAMULAB49 demonstrated desired characteristics such as Gram-positive, negative catalase activity, phenol tolerance, gastrointestinal conditions, hydrophobicity (65.71%), and autoaggregation (77.76%). Coaggregation activity against Micrococcus luteus, Pseudomonas aeruginosa, and Salmonella enterica serovar Typhimurium was observed. Molecular characterization revealed significant antioxidant activity in Levilactobacillus brevis RAMULAB49, with ABTS and DPPH inhibition rates of 74.85% and 60.51%, respectively, at a bacterial cell concentration of 109 CFU/mL. The cell-free supernatant exhibited substantial inhibition of α-amylase (56.19%) and α-glucosidase (55.69%) in vitro. In silico studies supported these findings, highlighting the inhibitory effects of specific organic acids such as citric acid, hydroxycitric acid, and malic acid, which displayed higher Pa values compared to other compounds. These outcomes underscore the promising antidiabetic potential of Levilactobacillus brevis RAMULAB49, isolated from fermented pineapple. Its probiotic properties, including antimicrobial activity, autoaggregation, and gastrointestinal conditions, contribute to its potential therapeutic application. The inhibitory effects on α-amylase and α-glucosidase activities further support its anti-diabetic properties. In silico analysis identified specific organic acids that may contribute to the observed antidiabetic effects. Levilactobacillus brevis RAMULAB49, as a probiotic isolate derived from fermented pineapple, holds promise as an agent for managing diabetes. Further investigations should focus on evaluating its efficacy and safety in vivo to consider its potential therapeutic application in diabetes management.